Evolutionary literacy as a catalyst for sustainable futures: connecting biological evolution education and education for sustainability - Patrícia Pessoa; J. Bernardino Lopes; Joelyn de Lima; Alexandre Pinto; Peter Søgaard Jørgensen; Xana Sá-Pinto (Evolution: Education and Outreach)
Abstract In the face of growing societal, public health and environmental challenges linked to the functioning of the biosphere, strong evolutionary literacy emerges as indispensable to plan and achieve sustainable futures. However, research on evolution education has mainly focused on the content taught in classrooms, leaving its application to sustainability issues largely unexplored. Given this, in this paper, we suggest an integrated view of biological evolution education and sustainability education. For that, we argue for the pivotal role of evolutionary literacy to address diverse sustainability issues and for the development of key competencies in sustainability, namely systems thinking and anticipatory competencies. To support the implementation in classrooms, we propose educational strategies to promote evolutionary literacy, systems thinking and anticipatory competencies through socioscientific issues linked to sustainability topics. Finally, we identify future research needed at the intersection of evolution education and education for sustainability to effectively promote evolutionary literacy and the development of key competencies in sustainability. With this, we aim to contribute to further enhancing education for sustainability through the lens of evolution.